2016
DOI: 10.1016/j.hlc.2016.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Periprocedural Management of Novel Oral Anticoagulants During Atrial Fibrillation Ablation: Controversies and Review of the Current Evidence

Abstract: Oral anticoagulation (OAC) has been the cornerstone for the prevention of thromboembolic complications in patients with atrial fibrillation (AF) at significant risk of stroke. Catheter ablation is an established efficacious technique for the treatment of AF. Ameliorating the risk of stroke or transient ischaemic attack (TIA) in patients with AF undergoing ablation requires meticulous planning of pharmacotherapy. The advent of non-vitamin K oral anticoagulants (NOACs) has broadened the therapeutic scope, repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…However, several other studies have concluded that dabigatran may safely be substituted for warfarin [2,9–11,13,15]. Although there are several articles that report an increase or decrease in adverse events with periprocedural DOACs, most studies find no remarkable differences in bleeding and thrombotic events between warfarin and DOACs [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, several other studies have concluded that dabigatran may safely be substituted for warfarin [2,9–11,13,15]. Although there are several articles that report an increase or decrease in adverse events with periprocedural DOACs, most studies find no remarkable differences in bleeding and thrombotic events between warfarin and DOACs [19].…”
Section: Discussionmentioning
confidence: 99%
“…If the patient remains in normal sinus rhythm 2–3 months after procedure, stopping long‐term anticoagulation can be considered. Importantly, failure to achieve and maintain a therapeutic INR in the previous 3 weeks or failure to achieve and maintain an ACT of > 300 seconds during the procedure have been associated with an elevated risk of thrombosis in the periprocedural window . It is against this historical backdrop that alternative management strategies for anticoagulation for ablation procedures can be considered in the present day.…”
Section: Prevention Of Thromboembolism Secondary To Catheter Ablationmentioning
confidence: 99%
“…Importantly, failure to achieve and maintain a therapeutic INR in the previous 3 weeks or failure to achieve and maintain an ACT of > 300 seconds during the procedure have been associated with an elevated risk of thrombosis in the periprocedural window. 38 It is against this historical backdrop that alternative management strategies for anticoagulation for ablation procedures can be considered in the present day. Although appropriate anticoagulation during AF catheter ablation is necessary to minimize thromboembolic risk, it also increases the risk of bleeding.…”
Section: Prevention Of Thromboembolism Secondary To Catheter Ablationmentioning
confidence: 99%
“…However, the failure to maintain a therapeutic INR over the preceding 3 weeks or to maintain an activated clotting time (ACT) of >300 seconds during ablation were associated with elevated thrombosis risk in the periprocedural window. 45 Current guidelines recommend 3 weeks of anticoagulation before catheter ablation in patients with AF ≥48 hours to mitigate thrombosis risk. 1 , 2 Alternatively, TEE may allow ablation to proceed without delay.…”
Section: Anticoagulation Protocols For Ablation Of Afmentioning
confidence: 99%